Multiperspective Islamic Study Methods: Practical Applications in a Psychological Review - Ningsih, Ade Cahya (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2024)
The purpose of this research is to describe various examples of the application of Islamic study methods in psychology. The author uses a descriptive qualitative method with a type of literature study approach. The data were obtained from documentation originating from various books, research journals, as well as various other documents or records that are worthy of being used as supporting material for obtaining scientific research data. In the process of data analysis, the writer took several stages that had to be carried out, namely (1) reading and examining various sources of data that had been obtained, (2) defining the nature of Islamic and psychological study methods, (3) analysing the relevance of Islamic study methods to psychology, and (4) concludes several applications of Islamic methods in psychological review. The results of the research found describe that the application of Islamic study methods in a psychological review consists of three points of discussion, namely (1) the 'iddah period for women, (2) the obligation to earn a living for men, and (3) the principle of child education based on the period development.